2004
DOI: 10.1108/09526860410557552
|View full text |Cite
|
Sign up to set email alerts
|

A new tool for measurement of process‐based performance of multispecialty tertiary care hospitals

Abstract: There is an increasing need of a model for the process-based performance measurement of multispecialty tertiary care hospitals for quality improvement. Analytic hierarchy process (AHP) is utilized in this study to evolve such a model. Each step in the model was derived by group-discussions and brainstorming sessions among experienced clinicians and managers. This tool was applied to two tertiary care teaching hospitals in Barbados and India. The model enabled identification of specific areas where neither hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Hariharan et al (2004) and Dey et al (2004) described how the AHP can be used to evaluate the performance of hospitals. Hariharan et al (2004) evaluated two tertiary care hospitals in Barbados and India, identified areas where each hospital did not perform well, and suggested recommendations for improvement. A questionnaire was used to help clinicians and managers to identify the most important evaluation factors.…”
Section: Health Care Evaluation and Policymentioning
confidence: 99%
“…Hariharan et al (2004) and Dey et al (2004) described how the AHP can be used to evaluate the performance of hospitals. Hariharan et al (2004) evaluated two tertiary care hospitals in Barbados and India, identified areas where each hospital did not perform well, and suggested recommendations for improvement. A questionnaire was used to help clinicians and managers to identify the most important evaluation factors.…”
Section: Health Care Evaluation and Policymentioning
confidence: 99%
“…Babic and Tomic-Plasibatalso (1999) incorporate CBA tools as criteria in evaluating investment projects. Haven (1998) Environmental Management (Ramcharan and Dey, 2005); and Quality Management (Hariharan et al 2004). …”
Section: Literature Reviewmentioning
confidence: 99%
“…It is believed that patient safety can be considered the ultimate goal of hospital supply chain [23,28]. Typical studies of patient safety are normally around mistakes and errors such as medication errors and wrong site surgery [29][30][31]. Errors are, however, not the only criteria in patient safety as asserted in [32][33][34].…”
Section: Patient Safetymentioning
confidence: 99%